2008
DOI: 10.1055/s-2008-1077028
|View full text |Cite
|
Sign up to set email alerts
|

Leukämoide Reaktion bei extrem unreifen Frühgeborenen

Abstract: Extremely immature preterm infants rarely present with a leukocytosis exceeding 30,000/microL. The pathogenetic sequence leading to leukemoid reactions in non-malignant diseases remains to be elucidated. Potential triggers for leukemoid reactions in premature infants include prenatal corticosteroids, chorioamnionitis and funisitis or systemic infection. In the two-year period from 2006 to 2007 all infants with a gestational age of less than 26 weeks were screened for leukocytosis. Among our cases, one preterm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The exact etiology and mechanism are unknown, and a differential diagnosis is usually challenging. However, this can occur as a result of infections (Streptococcus agalactiae, Escherichia coli, Listeria monocytogenes, Clostridioides difficile, and others), carcinomas, severe hemorrhage, following exposure to certain drugs, such as corticosteroids, and it also has been reported in preterm infants without any identifiable cause [7-9]. A negative CRP does not rule out the possibility of bacterial infection in children [10].…”
Section: Discussionmentioning
confidence: 99%
“…The exact etiology and mechanism are unknown, and a differential diagnosis is usually challenging. However, this can occur as a result of infections (Streptococcus agalactiae, Escherichia coli, Listeria monocytogenes, Clostridioides difficile, and others), carcinomas, severe hemorrhage, following exposure to certain drugs, such as corticosteroids, and it also has been reported in preterm infants without any identifiable cause [7-9]. A negative CRP does not rule out the possibility of bacterial infection in children [10].…”
Section: Discussionmentioning
confidence: 99%
“…These various clinical presentations have been described in neonates with congenital leukaemia 19. In contrast, no short-term organ dysfunction has been observed in neonates with leukemoid reaction 2 15. However, several studies have shown that prematures with leukemoid reaction, compared with peers without leukemoid reaction, have an increased risk of developing a bronchopulmonary dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…We now know that chorioamnionitis and funisitis4 12 or perinatal infection13–15 are also causes of leukemoid reaction. The average length of this reaction is 1.5–32 days 2 6 9 15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperleukocytosis is the state where white blood cell counts are more than 100,000/cumm. The overall incidence of a leukemoid reaction is less in the newborn period (around 15%) [2,3]. Holland and Maurer in 1963 reported the first cases of a leukemoid reaction in neonates.…”
Section: Introductionmentioning
confidence: 99%